Community perception and utilization of services for the severe wasted children aged 6–59 months in the Forcibly Displaced Myanmar Nationals and their nearest host communities in Bangladesh: a qualitative exploration - Rahman, Mahfuzur; Naila, Nurun Nahar; Islam, Md. Munirul; Mahfuz, Mustafa; Alam, Aklima; Karmakar, Gobinda; Ferdous, Anjuman Tahmina; Siddique, Muhammad Abu Bakr; Mustaphi, Piyali; Ahmed, Tahmeed (Frontiers in Nutrition, 2024)
There is a paucity of data on community perception and utilization of services for wasted children in Forcibly Displaced Myanmar Nationals (FDMN) and their nearest host communities. We conducted a qualitative study to explore community perceptions and understand the utilization of services for severely wasted children among the FDMN and their nearest host communities in Teknaf, Cox's Bazar. We carried out 13 focus group discussions and 17 in-depth interviews with the caregivers of the children of 6-59 months, and 8 key informant interviews. Caregivers' perceived causes of severe wasting of their children included caregivers' inattention, unhygienic practices, and inappropriate feeding practices. However, the context and settings of the FDMN camps shaped perceptions of the FDMN communities. Caregivers in both the FDMN and host communities sought care from healthcare providers for their children with severe acute malnutrition (SAM) when they were noticed and encouraged by their neighbors or community outreach workers, and when their SAM children suffered from diseases such as diarrhea and fever. Some caregivers perceived ready-to-use therapeutic food (RUTF) as a food to be shared and so they fed it to their non-SAM children. Caregivers of the children having SAM with complications, in the FDMN and host communities, were reluctant to stay in stabilization centers or complex respectively, due to their households' chores and husbands' unwillingness to grant them to stay. The findings of this study are expected to be used to design interventions using locally produced RUTF for the management of SAM children in the FDMN, as well as to inform the health sector working on SAM child management in the host